Drug priming enhances radiosensitivity of adamantinomatous craniopharyngioma via downregulation of survivin - Stache, Christina; Bils, Christiane; Fahlbusch, Rudolf; Flitsch, Joerg; Buchfelder, Michael; Stefanits, Harald; Czech, Thomas; Gaipl, Udo; Frey, Benjamin; Buslei, Rolf; Hoelsken, Annett (Neurosurgical Focus, 2016)
OBJECTIVE In this study, the authors investigated the underlying mechanisms responsible for high tumor recurrence rates of adamantinomatous craniopharyngioma (ACP) after radiotherapy and developed new targeted treatment protocols to minimize recurrence. ACPs are characterized by the activation of the receptor tyrosine kinase epidermal growth factor receptor (EGFR), known to mediate radioresistance in various tumor entities. The impact of tyrosine kinase inhibitors (TKIs) gefitinib or CUDC-101 on radiation-induced cell death and associated regulation of survivin gene expression was evaluated. METHODS The hypothesis that activated EGFR promotes radioresistance in ACP was investigated in vitro using human primary cell cultures of ACP (n = 10). The effects of radiation (12 Gy) and combined radiochemotherapy on radiosensitivity were assessed via cell death analysis using flow cytometry. Changes in target gene expression were analyzed by quantitative real-time polymerase chain reaction (qRT-PCR). Survivin, identified in qRT-PCR to be involved in radioresistance of ACP, was manipulated by small interfering RNA (siRNA), followed by proliferation and vitality assays to further clarify its role in ACP biology. Immunohistochemically, survivin expression was assessed in patient tumors used for primary cell cultures. RESULTS In primary human ACP cultures, activation of EGFR resulted in significantly reduced cell death levels after radiotherapy. Treatment with TKIs alone and in combination with radiotherapy increased cell death response remarkably, assessed by flow cytometry. CUDC-101 was significantly more effective than gefitinib. The authors identified regulation of survivin expression after therapeutic intervention as the underlying molecular mechanism of radioresistance in ACP. EGFR activation promoting ACP cell survival and proliferation in vitro is consistent with enhanced survivin gene expression shown by qRT-PCR. TKI treatment, as well as the combination with radiotherapy, reduced survivin levels in vitro. Accordingly, ACP showed reduced cell viability and proliferation after survivin downregulation by siRNA. CONCLUSIONS These results indicate an impact of EGFR signaling on radioresistance in ACP. Inhibition of EGFR activity by means of TKI treatment acts as a radiosensitizer on ACP tumor cells, leading to increased cell death. Additionally, the results emphasize the antiapoptotic and pro-proliferative role of survivin in ACP biology and its regulation by EGFR signaling. The suppression of survivin by treatment with TKI and combined radiotherapy represents a new promising treatment strategy that will be further assessed in in vivo models of ACP.
EVALuna2:7353